Without Affection or Enthusiasm' Problems of Involvement and Attachment in `Responsive' Public Management - Gay, Paul Du (Organization (London, England), 2008)
The paper focuses on the changing ethical template that programmes of `responsive' or `entrepreneurial' managerial reform require of civil servants. Contemporary demands for responsive public management contain two emotional injunctions to public bureaucrats. The first, derived from populist doctrines of political right, requires bureaucrats to be responsive to the needs of their `clients'. In the name of `recognition' and the `politics of care', for example, it is thought vital to inculcate in bureaucratic conduct a sense of `compassion' or close identification with others' feelings. Secondly, in the name of responsiveness to political superiors and the delivery of their policy objectives, bureaucrats are expected to exhibit `ownership' of and identification with particular policies. They are required to be committed champions for and enthusiastic advocates of those policies. Both of these injunctions are deemed to be more in tune with democratic principles and the currents of contemporary ethical culture (`diversity' or `human rights', for example) than what is represented as the unlamented Weberian world of rule-bound hierarchy. The paper seeks to question this assessment.